1974
DOI: 10.1002/bms.1200010203
|View full text |Cite
|
Sign up to set email alerts
|

Reagent gases for G.C.-M.S. analyses

Abstract: Abstract-Several reagent gases and mixed reagent gases for high pressure ion-molecule reaction ionization of samples have been investigated for use in gas chromatography-mass spectrometry analyses. The common g.c. carrier gases and their mixtures with other gases suchas isobutane, ammonia. tetramethylsilane, hexafluoroacetone and nitric oxide, were studied. These reagents were used to enhance the molecular ion intensity and to simpiify the spectra of steroidal alcohols and the trimethylsilyl ethers of biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Jelus et al () using nitrogen/(CH 3 ) 4 Si mixtures under CI conditions failed to observe [M+73] + ions from dihydrocholesterol whose spectrum exhibited [M − TMS‐OH] + ions. Use of (CH 3 ) 3 SiOSi(CH 3 ) 3 also failed to produce [M+73] + ions from steroidal alcohols and the authors concluded that, for some classes of compounds, chemical ionization would not give the required ions even in the presence of the high‐pressure conditions of the experiment that should have provided collisional cooling and stabilization of the [M+73] + ions.…”
Section: Inter‐molecular Reactions Of Siliconium Ionsmentioning
confidence: 99%
“…Jelus et al () using nitrogen/(CH 3 ) 4 Si mixtures under CI conditions failed to observe [M+73] + ions from dihydrocholesterol whose spectrum exhibited [M − TMS‐OH] + ions. Use of (CH 3 ) 3 SiOSi(CH 3 ) 3 also failed to produce [M+73] + ions from steroidal alcohols and the authors concluded that, for some classes of compounds, chemical ionization would not give the required ions even in the presence of the high‐pressure conditions of the experiment that should have provided collisional cooling and stabilization of the [M+73] + ions.…”
Section: Inter‐molecular Reactions Of Siliconium Ionsmentioning
confidence: 99%
“…Neopentane produces similar positive CI spectra to isobutane and doubles the electron filament lifetime [20] but is many times more expensive than isobutane to obtain at high purity. Dilution of deleterious analytical gases, including isobutane with inert gases, has been performed for CI [29][30][31][32], but the experiments were not constructed for isobutane to directly interact with an analyte. In the present research, a reagent gas mixture of isobutane diluted in argon produces positive CI and EC-NCI spectra of equal or better quality to pure isobutane.…”
Section: Introductionmentioning
confidence: 99%
“…7-1.0 Torr. The technique for the mix-h i b i t e d .ing of reagent gases for chemical ionization experiments has been described 15. …”
mentioning
confidence: 99%